A storm of images : iconoclasm and religious reformation in the Byzantine world - Jenkins, Philip., 1952- (Waco : : Baylor University Press, 2023)
"Surveys the iconoclastic controversy of the eighth and ninth centuries, describing the events and controversies and analyzing the polemic, while also exploring the theological issues raised"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher
Keywords: Iconoclasm -- Byzantine Empire; Icons, Byzantine; Byzantine Empire -- Church history